Pyocyanin, a Metabolite of Pseudomonas Aeruginosa, Exhibits Antifungal Drug Activity Through Inhibition of a Pleiotropic Drug Resistance Subfamily FgABC3 - Houshaymi, Bilal; Awada, Rana; Kedees, Mamdouh; Soayfane, Zeina (Drug Research, 2019)
The fungus Fusarium graminearum is the causative agent of economically significant plant diseases such as Fusarium Healed Blight (FHB) of cereals, its mycotoxins as deoxynivalenol (DON), Nivalenol (NIV) and Zearalenone (ZEN) contaminate wheat and other grains. The objectives of the present study were to determine the mechanism by which the bacterium Pseudomonas aeruginosa inhibits the growth of F. graminearum. Our results indicate that P. aeruginosa metabolites as pyocyanin has effective antifungal properties. Pyocyanin was produced by P. aeruginosa when cultured on mineral salt medium and reached a maximum concentration after 72 h. Pyocyanin significantly decreased mycotoxins of F. graminearum, a 25 mg/ml of pyocyanin for 72 h decreased DON by 68.7% and NIV by 57.7%.Real-Time PCR analysis demonstrated that the antifungal effect is mediated by downregulation of the Pleiotropic Drug Resistance (PDR) subfamily FgABC3. 25 mg/ml of pyocyanin decreased FgABC3-mRNA by 60%, inhibited the fungal growth and decreased the area of mycelial growth at 12, 24, 36 and 72 h post incubation by 40–50%. Deletion of FgABC3 led to enhanced accumulation of DON and NIV by 40 and 60%, respectively.The data presented in this report may have significance in understanding mechanism by which certain bacterial metabolites exert a beneficial effect and for developing antifungal drugs.
Keywords: Fusarium graminearum; Pseudomonas aeruginosa; Pyocyanin; mycotoxins; FgABC3